Estratégias para brand equity de marca de moda feminina através das ferramentas do marketing digital - Costa, Grazielle Barros (2019)
The present work aims to analyze the building strategies of the branding equity of a female fashion brand through the digital marketing tools. To achieve this objective, it was necessary to identify the brand-building strategies that apply to women's fashion retailing; identify digital platforms that are used in it and understand how marketing platforms digitally contribute to the brand equity of women's fashion brands. This research is a case study of the Linge brand that served as the basis for data collection, being subdivided into two types of research: exploratory and qualitative, through in-depth interviews with managers of the Linge brand and descriptive and quantitative, through a form answered by 236 brand consumers. The results indicate that the strategies used to build branding equity are mainly through Instagram, and some of these strategies are: associations with digital influencers, ad boost and personalized online servisse. As for the questions made in the quantitative phase, they tended to confirm the methods listed in the in-depth interview with Linge brand managers.